Pessoa com deficiência e sua inclusão na instrução escolar - RODRIGUES, Denis Leite (Centro Universitário UNIFAFIBE, 2023)
This article aims to analyze school inclusion as a recognized prerogative for people with disabilities in general, and those with autistic spectrum disorder - ASD in particular. To this end, there are initially considerations concerning the principle of the dignity of the human being, an institute that is expressly provided for in the Brazilian Constitution (article 1, caput and item III), as one of the foundations of the Federative Republic of Brazil, and thus it ends up basing the whole homeland legal order. In the following, it will focus on the international and Brazilian legislation related to this theme, culminating with the advent of the Brazilian Inclusion Law (or Statute of the Disabled People), which will try to identify the gradual evolution of the concept of school inclusion and the extent to which the issue of international norms was decisive for the emergence of relevant Brazilian law. The research for the writing of this article was conducted through consultation with legislative and doctrinal sources, and, whenever appropriate, reference to jurisprudential considerations, as a way of reinforcing legal and doctrinal arguments. It may be concluded at the end of the foregoing considerations that, despite the generally unfortunate slowness difficulty of fully implementing the normative commandments concerning this range of prerogatives concerning persons with disabilities, there is a remarkable normative evolution, linked to this rights area.